2019
DOI: 10.1051/e3sconf/20199204005
|View full text |Cite
|
Sign up to set email alerts
|

A semi-empirical relationship for the small-strain shear modulus of soft clays

Abstract: The small-strain shear modulus (Gmax) is a soil property that has many practical applications. The authors compiled a database of Gmax measurements for 40 normally consolidated to slightly overconsolidated low to high plasticity clays. Using these data, the authors propose a semi-empirical relationship between Gmax, effective stress (σ'v or σ'c), preconsolidation stress (σ'p) and in-situ void ratio (e0) for four ranges of plasticity index (Ip): Ip < 30%, 30% ≤ Ip < 50%, 50% ≤ Ip < 80% and 80% ≤ Ip <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Therefore, comprehensive studies of the Gmax have been conducted in the early 1970's, leading to the development of the resonant column apparatus (Hardin & Richart, 1963). Past studies have found that the small Gmax is mainly related to the effective stress and void ratio (Taukoor et al, 2019;Santamarine et al, 2001;Mitchell and Soga 2005).…”
Section: A Review Of Small Strain Shear Modulusmentioning
confidence: 99%
“…Therefore, comprehensive studies of the Gmax have been conducted in the early 1970's, leading to the development of the resonant column apparatus (Hardin & Richart, 1963). Past studies have found that the small Gmax is mainly related to the effective stress and void ratio (Taukoor et al, 2019;Santamarine et al, 2001;Mitchell and Soga 2005).…”
Section: A Review Of Small Strain Shear Modulusmentioning
confidence: 99%